FAKTOR RISIKO KEJADIAN STUNTING PADA ANAK BALITA USIA 24-59 BULAN (Studi Kasus di Wilayah Kerja Puskesmas Gabus II Kabupaten Pati Tahun 2017) - Astutik Astutik; M. Zen Rahfiludin; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2018)
Stunting is a malnutrition chronic caused by poor nutrient intake for long periods of time due to inappropriate feeding of nutritional needs. A prevalence of stunting in Indonesia was 37,2 %. Gabus II Community Health Centers is one of the areas with high prevalence of stunting in 2015 was 30.36%. The purpose of this study was conducted to dertermine the realtionship between low birth weight, economic status and intake of nutrient with stunting in children aged 24-59 months in Gabus II Community Health Centers. This research use a kind of analytic observational with case control design. Sample were selected using a technique of purposive sampling with the number of each group were 33 respondents. Analysis of data using chi square. The results showed that there was correlation between level of family prosperity (p = 0,003, OR = 5,333), protein intake (p = 0,026, OR = 3,538) and zinc (p = 0,012, OR = 4,241) with stunting incidence and all three were stunting risk factors. Low birth weight variables were not associated with stunting events but is a risk factor for stunting, (p = 0.319, OR = 1.647). Other variables such as energy intake, iron, calcium, and vitamin A had no significant association with stunting events. Community Health Centers need to do nutritional educationand monitor the nutritional status regularly and periodically, so that it can be done as early as possible prevention or prevention of stunting in toddlers. Mother should be more active following posyandu activities and pay attention to diet so that nutritional adequacy is fulfilled.